Behaviour of reinforced concrete beam with silica fume under dynamic loading / Rudy Tawie Joseph Sipi - Rudy Tawie Joseph Sipi (Faculty of Civil Engineering, 1999)
Concrete mixes design to produce 42 N/mm² - 84 M/mm² in compressive strength are easily obtainable today with silica fume replacing a portion of the cement content. Such concretes with a design compressive strength exceeds 42 M/mm² may be defined as “High Strength Concrete”. For several reasons, there has recently been a marked interest in the determination of the dynamic characteristics of structures and their response under dynamic loads and effect. Subjected to dynamic loading under sinusoidal wave pattern, a study has been carried out to make an experimental investigation on reinforced concrete beam (Grade 60 N/mm2) incorporating silica fume replacing cement by weight of w/c ratio of 0.30, with respect to the serviceability and ultimate limits. A total of three specimens each with different silica fume proportion (8%, 12% and 16%) by weight of cement were cast and tested under the dynamic load. Parameters investigated include deflections, crack widths and crack lengths.